1988
DOI: 10.1099/00221287-134-11-2993
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Control of the Respiratory System in the Dimorphic Fungus Mucor rouxii

Abstract: Spores of Mucor rouxii had low levels of respiratory activity partially sensitive to cyanide and salicylhydroxamic acid (SHAM). They contained a full set of cytochromes but in low concentrations, especially cytochromes aa3. Aerobic growth induced a rapid increase in respiratory activity resistant to SHAM but fully sensitive to cyanide, and in the levels of cytochromes, mainly cytochromes aaj. These processes were subject to catabolite repression. Incubation under anaerobic conditions, independent of cell morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Anaerobically grown yeasts of M. genevensis reportedly possess mitochondria with well-defined cristae, although they were said to lack cytochromes (47). More recently, the same complement of cytochromes was shown to exist in both aerobic hyphae and anaerobic yeasts of M. rouxii (38). Fully developed mitochondria exist in yeasts of M. racemosus grown under a nitrogen atmosphere (108a).…”
Section: Carbon and Energy Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobically grown yeasts of M. genevensis reportedly possess mitochondria with well-defined cristae, although they were said to lack cytochromes (47). More recently, the same complement of cytochromes was shown to exist in both aerobic hyphae and anaerobic yeasts of M. rouxii (38). Fully developed mitochondria exist in yeasts of M. racemosus grown under a nitrogen atmosphere (108a).…”
Section: Carbon and Energy Metabolismmentioning
confidence: 99%
“…Furthermore, the respiratory capacity of these cells is nearly as high as it is in aerobically grown hyphae (150b chondria isolated from anaerobic yeasts of M. racemosus do not lack any proteins extractable from mitochondria of aerobic hyphae (108a). Because the phospholipid composition of mitochondria differed in yeasts and hyphae of M. genevensis (85) and because cerulenin inhibits yeast-tohypha morphogenesis and attendant changes in cell phospholipid composition (105), it has been suggested that there may be some nonrespiratory function of the mitochondrion required for hyphal development (38,44,105).…”
Section: Carbon and Energy Metabolismmentioning
confidence: 99%
“…In C. parapsilosis, respiration type insensitive to antimycin A and sensitive to high concentration of SHAM was found (Milani et al, 2001;Guerin and Camougrand 1994) and it was proposed that it corresponds to activity of respiratory chain parallel with classical one, with partitioning point of electron flux at the level of ubiquinone (Milani et al 2001). Also, In M. rouxii (Cano-Canchola et al 1988) fungus closely related to P. blakesleeanus, additional cytochrome (cyto), which is not the part of classical respiratory chain, was detected. Having in mind results presented for C. parapsilosis and M. rouxii it may be assumed that P. blakesleeanus expresses a third type of respiration, but further investigations concerning molecular basis of the observed respiration type should be performed.…”
Section: Discussionmentioning
confidence: 95%
“…In spite of this, respiration pathways of Zygomycota are the least investigated among fungi so far. Alternative respiration was investigated in only two species of Zygomycota, M. rouxii (Cano-Canchola et al 1988;Salcedo-Hernandez et al 1994) and A. macrogynus (Heldt-Hansen et al 1983a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Several examples have been reported, especially within Mucoromycotina (Cano-Canchola et al, 1988; Salcedo-Hernandez et al, 1994) which are phylogenetically closely related to AMF (Hibbett et al, 2007), showing a respiratory shift characterizing spore germination process from AOX (dormancy) to COX (hyphal growth). It is difficult to define AOX/COX interplay during spore germination in R. irregulare as spores can return into dormancy and germinate again several times without obvious phenotypic signs (Giovanetti et al, 2010), and the hyphal tube germination is the physiological consequence of an already implemented respiratory shift, as shown for Mucor rouxii (Cano-Canchola et al, 1988). …”
Section: Discussionmentioning
confidence: 99%